Sustainable Supply Management in SMEs: Evidence from the Finnish textile industry - Kullas, Tiia (My University, 2018)
This study examines the phenomenon of sustainable supply management among small and medium-sized enterprises operating in the Finnish textile industry. Major environmental challenges as well as increasing stakeholder pressure compel the firms to address the sustainability impact of their actions, and to engage in sustainable practices that involve managing the economic, environmental as well as social performance of the firm. Moreover, due to globalization and extensive increase in outsourcing, firm’s responsibility extends beyond its own borders and direct control, as companies are increasingly held responsible also for their suppliers’ actions. Thus, it is relevant to study how the buyer firms can manage sustainability in their upstream supply chains. Previous research has studied the phenomenon mainly from the perspective of large corporations, and the research addressing how the SMEs can integrate sustainability into their supply management remains limited. The research is initiated by conducting an extensive literature review on the phenomenon of sustainable supply management, taking also the characteristics of SMEs as well as the challenging nature of the textile industry into consideration. Based on the literature review, theoretical framework of the study is formulated to guide the empirical research. The empirical part of the research employs a research strategy of an extensive case study. The empirical data is collected through theme interviews with the representatives of six small and medium-sized enterprises operating in the Finnish textile industry, and the data is analysed by employing a theory-bonded content analysis. The main findings of the study indicate that sustainability is viewed as an increasing trend in the textile industry. The SMEs consider sustainability as an integral part of their identity, brand and firm values, and also increasingly recognize the positive impact of sustainable practices on the economic benefits of the business. The motivation to manage sustainability in relation to suppliers was found to mainly derive from the internal aspiration of the SMEs as well as from the increasing consumer awareness. Despite the various challenges originating from the nature of the industry as well as the characteristics of SMEs, the textile SMEs rather proactively engage in sustainable supply management through careful supplier selection, active development, close and long-term collaboration as well as continuous assessment. This thesis contributes to the existing research by examining how the SMEs can manage sustainability in relation to their suppliers, as well as by addressing the motivational factors and perceived challenges behind the firms’ sustainability efforts. Regarding the managerial contribution of the study, this thesis provides suggestions for the SMEs of how to overcome the challenges derived from the low negotiating power and how to increase the ability to influence the sustainability performance of the suppliers. Overall, the SMEs should aim at developing direct and close supplier relationships with a long-term orientation to efficiently drive sustainable development forward in the textile industry.
Keywords: Sustainability; sustainable supply management; small and medium- sized enterprises; textile industry; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master’s Programme in Strategic Business Development|